Hubungan KEK dengan Anemia Gravidarum pada Ibu Riwayat BBLR - Arie Alfina Mahmudian; Dian Aby Restanty; Sugijati Sugijati (Puslitbang Sinergis Asa Professional, 2021)
KEK (Chronic Energy Deficiency) is a condition of the mother suffering from lack of calories and protein (malnutrition) that lasts chronic (chronic) at risk of causing complications in the mother one of which is anemia gravidarum. Anemia in pregnancy is a decrease in Hb levels, so that the carrying capacity of oxygen for the needs of vital organs in the mother and fetus is reduced. The purpose of this study is to determine the relationship of KEK with anemia gravidarum in mothers with low birth weigth history. The correlation analytic research design is a case control study approach, the population is 68 mothers with low birth weight history, using simple random sampling technique, the sample is calculated using Slovin formula, the number of 58 low birth weight history mothers fulfills the inclusion criteria. The research instrument used observation sheets to look at secondary data on cohorts of pregnant women, data analysis using the chi square test obtained a p value of 0, 001 means that p <0.05 indicates the relationship of KEK with anemia gravidarum in women with low birth weight history with a close relationship is sufficient. The value of the Contingency Coefficient in the Chronic Energy Deficiency variable is 0.39, which means that the relationship between KEK and anemia gravidarum is sufficient. The Odds Ratio (OR) value in the Chronic Energy Deficiency variable is 6.9, which means that pregnant women with nutritional status of Chronic Energy Deficiency have a 6.9 times greater risk of anemia during pregnancy than those who are not. Inadequate nutritional needs have a greater risk of anemia during pregnancy and the risk of giving birth to Low Birth Weight Babies. Researchers suggest providing counseling to women of adolescence, women of childbearing age and especially pregnant women so that they can add more information about the importance of nutritional status in pregnant women, the dangers of anemia during pregnancy and also the importance of consuming blood booster tablets during pregnancy. So that it is expected to reduce the incidence of anemia pregnant women case and low birth weight history.